An Exploration of the Applications, Challenges, and Success Factors in AI-Driven Product Development and Management - Witkowski Aron; Wodecki Andrzej (Foundations of Management)
While extensive research studies exist on the influence of AI solutions on organizations as a whole, there is a paucity of comprehensive studies examining the adoption of these solutions in product development and subsequent management processes. This article presents an exploratory investigation of the applications, challenges, and determinants of success associated with artificial intelligence (AI) solutions employed in the product development and management processes. To this end, a qualitative thematic analysis is conducted based on twelve in-depth interviews with experts proficient in AI engineering and product management, representing twelve distinct organizations within the Polish IT sector. This article offers insights into four potential applications and expounds on various factors impacting the challenges and success of deployed AI solutions, generating two additional emergent themes. This article delineates practical implications for organizations and product managers and proposes intriguing directions for future research exploring topical areas of study.